Quasi-Dirac neutrinos in a model with local B - L symmetry - Machado, A. C B [UNESP]; Pleitez, V. [UNESP] (IOP Publishing, 2013)
In a model with B - L gauge symmetry, right-handed neutrinos may have exotic local B - L charge assignments: two of them with B - L = -4 and the other one having B - L = 5. Then, it is natural to accommodate the right-handed neutrinos with the same B - L charge in a doublet of the discrete S3 symmetry, and the third one in a singlet. If the Yukawa interactions involving right-handed neutrinos are invariant under S3, the quasi-Dirac neutrino scheme arises naturally in this model. However, we will show how in this scheme it is possible to give a value for θ13 in agreement with the Daya Bay results. For example the S3 symmetry has to be broken in the Yukawa interactions involving right-handed charged leptons. © 2013 IOP Publishing Ltd.